Karakteristik Intensitas Curah Hujan Yang Terjadi Di Kota Bengkulu Pada Tahun 2016 – 2021 - Fevi Wira Citra; Nurmintan Silaban; Dihamri Dihamri (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2022)
The climate of Bengkulu City is strongly influenced by the Indian Ocean, if there is low pressure in the Indian Ocean, Bengkulu City will experience heavy rains, even accompanied by lightning and storms High rainfall that occurred in Bengkulu City in 2016 occurred in March reaching 641 mm, and in 2020 in November it reached 609 mm/year. The amount of rainfall intensity varies due to the duration of rainfall or the frequency of its occurrence. The climate classification in Indonesia according to Schmidt Ferguson is based on a comparison between dry months (BK) and wet months (BB). BK: months with rainfall less than 60 mm, BB: months with rainfall greater than 100 mm, and Humid Months: months with rainfall between 60-100 mm. The research used is quantitative. The data used is monthly rainfall data from the Climatology Station of Pulau Baai Bengkulu. The data used is monthly rainfall data for a period of 6 years in the period 2016 - 2021. Wet months only occurred in 2018 and 2019. In 2018 it was in the condition of type A rain which was very wet at 9.09 and type C rain a rather wet one of 42.85 which only happened in 2019.